Estimated Tree Carbon Reserves and Saplings in the Nagari Sumpur Kudus Social Forestry Area, Sijunjung Regency - Amanda, Falencia Mauri; Chairul, Chairul; Solfiyeni, Solfiyeni; Mukhtar, Erizal (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The forest within The Social Forestry of Nagari Sumpur Kudus, Sijunjung Regency has the ability to store carbon reserves. The forest area located in the highlands shows a lot of biodiversity, influenced by the ability of the forest to maintain carbon stocks and diverse plant species in the area. The purpose of this study is to determine the total biomass and total carbon stocks stored in the Social Forestry Area of Nagari Sumpur Kudus, Sijunjung Regency. This research was conducted from May to October 2023. Taking at tree and sapling strata uses a nondestructive sampling method. From the results, it is obtained that the three strata are as many as 14 families and 14 species. The sapling strata is obtained from as many as 17 families and 37 species. The total above-ground biomass is l78,97 ton/ha consisting of 177,83 ton/ha tree biomass and 1,13 ton/ha sapling biomass. The total above-ground carbon stock is 86,11 ton/ha consisting of tree carbon stock 85,58 ton/ha and sapling carbon stock 0,53 ton/ha. The Social Forestry Area of Nagari Sumpur Kudus, Sijunjung Regency has the potential to store carbon stocks which is included in the medium category and need to be maintained.